2021
DOI: 10.1177/21582440211052951
|View full text |Cite
|
Sign up to set email alerts
|

Research on Social Media Content Marketing: An Empirical Analysis Based on China’s 10 Metropolis for Korean Brands

Abstract: Drawing from the Uses and Gratifications Theory (UGT), this study explores the influences of the gratifications derived from the use of the WeChat on Chinese consumers’ purchase intention for South Korean brands. A total of 2,276 respondents from ten cities in China—Beijing, Shanghai, Guangzhou, Shenzhen, Ji’nan, Nanjing, Zhengzhou, Wuhan, Chengdu, and Xi’an—were part of this study. Structural equation modeling (SEM) and PROCESS analysis was applied to examine the data. Gratifications that Chinese consumers re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 96 publications
(116 reference statements)
1
10
1
Order By: Relevance
“…Thus, the variable of health literacy needs to be analyzed further to test the aspect of validity and reliability in accordance with the last research. This new variable of service provider interaction creates a new framework that contributes to adding a new variable to the last research that analyzed social media content marketing (Chen & Shen, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Thus, the variable of health literacy needs to be analyzed further to test the aspect of validity and reliability in accordance with the last research. This new variable of service provider interaction creates a new framework that contributes to adding a new variable to the last research that analyzed social media content marketing (Chen & Shen, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The primary aim of this study was to analyze antecedents of Customer Engagement (CE) towards Customer Usage Intention (CUI) and Positive E-WOM (PEW) with Health Literacy (HL) as the moderating effect. The question of health literacy was derived based on the source cited in references (Chen & Shen, 2021) and modified by the respondent's understanding.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Non-networked local television station managers realize that they may be unable to compete in terms of advertising revenue with networked national mainstream television stations, especially when new advertising media is developing in internet-based media [26]. Informant Y1 (ABTV) revealed that local television cannot compete for advertising revenue with national television because their ratings are still inferior.…”
Section: Other Legitimate Business Development and Collective Strategiesmentioning
confidence: 99%